Factors Associated with Newborn Asphyxia at Dr. Harjono Hospital, Ponorogo, East Java - Purwaningsih, Yustina; Dewi, Yulia Lanti Retno; Indarto, Dono; Murti, Bhisma (Journal of Maternal and Child Health, 2018)
Background: Asphyxia, or perinatal asphyxia, refers to oxygen deprivation during labor or delivery long enough to cause physical harm, and particularly brain damage. When birth asphyxia is severe, it can injure brain cells and cause potentially fatal conditions, including Hypoxic-Ischemic Encephalopathy (HIE), brain injuries, seizures, and cerebral palsy. This study aimed to investigate factors associated with newborn asphyxia at Dr. Harjono Hospital, Ponorogo, East Java. Subjects and Method: This was a case-control study conducted at perinatology ward, Dr. Harjono Hospital, Ponorogo, East Java, in July 2018. A sample data of 360 newly born infants between January 2017 and December 2017 was selected for this study by fixed disease sampling, comprising 180 newborns with asphyxia and 180 newborns without asphyxia. The dependent variable was birth asphyxia. The independent variables were low birthweight, prematurity, and post date. The secondary data were obtained from the medical record and analyzed by a multiple logistic regression.Results: The risk of asphyxia increased with low birthweight (OR= 4.45; 95% CI= 2.17 to 9.10; p<0.001), prematurity (OR= 4.83; 95% CI= 2.41 to 9.67; p<0.001), and post date (OR= 2.52; 95% CI= 1.31 to 4.81; p= 0.005).Conclusion: The risk of asphyxia increases with low birthweight, prematurity, and post date.Keywords: asphyxia, neonate, low birthweight, prematurity, post dateCorrespondence:Yustina Purwaningsihi. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami No. 36 A, Surakarta 57126, Central Java. Email: yustinapurwaningsih202@gmail.comJournal of Maternal and Child Health (2018), 3(4): 287-293https://doi.org/10.26911/thejmch.2018.03.04.06